Improvement of biogas upgrading process using chemical absorption at ambient conditions - Abdeen, Fouad RH; Mel, Maizirwan; Jami, Mohammed Saedi; Ihsan, Sany Izan; Ismail, Ahmad Faris (Penerbit UTM Press, 2018)
Biogas major components are methane, carbon dioxide and traces of hydrogen sulfide, ammonia and nitrogen. Biogas upgrading process is the process by which carbon dioxide (composing 40 % of the biogas) is removed. In this study chemical absorption process using three different solvents (10 – 30 % monoethanolamine, 4 – 12 % sodium hydroxide and 5 – 15 % aqueous ammonia) was performed to produce methane-enriched biogas. A laboratory-scale packed-column apparatus containing efficient and cheap packing material (plastic bioball) was used to perform the experimental work in this study. Initial absorption runs were performed to select the best solvent type and concentration. Monoethanolamine (MEA) was proven to have the highest ability in producing upgraded biogas using a single absorption column apparatus at ambient conditions. The liquid to gas flow ratio was investigated using 30 % MEA solution. Optimum liquid to gas flow ratio for biogas upgrading process was determined to be about 18 (on mass basis). Biogas with methane content up to 96.1 v/v% was produced with CO2 loading capacity up to 0.24 mole-CO2 per mole-MEA.